PENGARUH INDEPENDENSI DAN EFEKTIVITAS KOMITE AUDIT TERHADAP MANAJEMEN LABA - Taufik Briliyan Novendi, 0725030095; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2013)
This research which testing and analysing influence of independency of audit committee, size of audit committee, meet frequency of audit committee and proportion of audit committee to earning management at manufacturing company which is go public in Indonesia. Population in this research is entire/all peripatetic company in sector of manufaktur which enlist in Effect Exchange Indonesia (BEI) Year 2008-2011. Technique intake of sampel use technique of purposive sampling with criterion as follows: (1) company which is launch annual report during period of perception, (2) financial statement presented in rupiah, (3) have a net profit report , and (4) owning complete data for this research. According to criterion which have been specified by there are 166. Technique analysis sampel the used is doubled regresi. Research result indicte that independency of audit committee size of audit committee have an effect on to earning management. While variable of independency of audit committee, meet frequency of audit committee and proportion of audit committee not have an effect on to earning management.Keywords: Independency of audit committee, Size of audit committee, Meet frequency of audit committee and Proportion of audit committee.